Consumption function under the permanent income hypothesis in selected Arab countries - Miloud Elwakshi; Ali Al-Qudah (Proceedings of AICS - Social Sciences, 2013)
This article estimates the consumption function under the permanent income hypothesis. The study is based on annual data covering the period from 1985 to 2010 for selected 10 Arab countries. The models specification implemented refer to the combined partial adjustment and adaptive expectations model, and the adaptive expectations model. The estimation results with respect to the consumption function under the permanent income hypothesis and the combined partial adjustment and adaptive expectations model were rather good only for some countries. Therefore, we demonstrated only the estimation outcomes for the consumption function model under the permanent income hypothesis and the adaptive expectations model. The results show strong support for the hypothesis, supporting thus the consumption function under the permanent income hypothesis and the adaptive expectations model.Keywords: Consumption Function, Permanent-Income Hypothesis, Arab Countries.